(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores the transformation of folklore elements within the poetics of twentieth-century modernism through a comparative analysis of Uzbek and Western literary traditions. Drawing on mythopoetic theory and archetypal criticism, the study examines how folklore motifs, myths, and archetypes are reinterpreted in modernist literature as symbolic and psychological structures rather than as manifestations of oral tradition. The research demonstrates that while Western modernism tends to universalize folklore as an expression of existential crisis and fragmentation, Uzbek modernist literature employs folkloric codes to preserve and reinterpret national identity within a modern aesthetic framework. The findings contribute to comparative literature studies by highlighting folklore as a shared yet culturally differentiated foundation of modernist poetics.